The Inhibitory Effect of Heparin and Related Glycosaminoglycans on Neutrophil Chemotaxis - Matzner, Yaacov; Marx, Gerard; Drexler, Ruth; Eldor, Amiram (Thrombosis and Haemostasis, 1984)
Clinical observations have shown that heparin has antiinflammatory activities. The effect of heparin on neutrophil chemotaxis was evaluated in vitro in the Boyden Chamber. This method enabled differentiation between the direct effects of heparin on neutrophil migration and locomotion, and its effects on chemotactic factors. Heparin inhibited both the random migration and directed locomotion of human neutrophils toward zymosan-activated serum (ZAS) and F-met-leu-phe (FMLP). Inhibition was found to be dependent on the concentrations of the heparin and of the chemotactic factors. No specific binding of heparin to the neutrophils could be demonstrated, and heparin’s inhibitory effects were eliminated by simple washing of the cells. When added directly to the chamber containing chemotactic factor, heparin inhibited the chemotactic activity of ZAS but not that of FMLP, suggesting a direct inhibitory effect against C5a, the principal chemotactic factor in ZAS.Experiments performed with low-molecular-weight heparin, N-desulfated heparin, dextran sulfate, chondroitin sulfate and dextran indicated that the inhibitory effects of heparin on neutrophil chemotaxis are not related to its anticoagulant activity, but probably depend on the degree of sulfation of the heparin molecule.
Keywords: Heparin; Neutrophil; Chemotaxis